As Good As Wood - I. Wan Asma (Kepong, Selangor Darul Ehsan, Malaysia : Forest Research Institute Malaysia : Ministry of Natural Resources and Environment, Malaysia, 2012)
Oil palm research and wood products in Malaysia.
In English.
Keywords: Oil palm; Oil palm -- Malaysia -- Congresses